Murottal Qur'an on Anxiety and Sleep Quality of Patients Undergoing Dialysis: Scoping Review - Putro, Dimas Utomo Hanggoro; Setiawan, Arifin; Wibowo, Arif Apriyanto; Sucipto, Muhamad Bayu; Fesanrey, Rian Andito; Sugandi, Veri (Jurnal Keperawatan, 2024)
Chronic kidney failure is a non-communicable disease problem that causes global problems. Patients with chronic kidney failure require dialysis therapy, one of which is hemodialysis. Chronic kidney failure patients undergoing hemodialysis may experience anxiety, depression, and decreased sleep quality. The purpose of this study was to determine the effect of murottal Al-Qur'an therapy on anxiety, depression, and quality of sleep in chronic kidney failure patients undergoing hemodialysis. The method used is scoping review with the Google Scholar database and Springer Link. The keywords used are Chronic Kidney Disease Patients" AND "Murottal Qur'an Therapy" OR "Holy Qur'an Therapy" AND "anxiety and sleep quality while undergoing hemodialysis. Inclusion criteria include full text articles from 2019-2023 in Indonesian or English published from national and international journals. The types of articles are Randomized Controlled Trial (RCT), Quasy Experimental, and Case Study. Twelve articles met the inclusion criteria. Al-Qur'an murottal therapy with surahs Ar-Rahman and Al-Fatihah can reduce anxiety and improve sleep quality because there are chemical elements in the body. The conclusion is that there is an effect of murottal Al-Qur'an on reducing anxiety and improving sleep quality in chronic kidney failure patients undergoing hemodialysis.